Antimicrobial Activity of Some Novel 1-(3-(4-Chlorophenylimino)-3,4-dihydroquinoxalin-2-yl)-3-substituted phenyl-1H-pyrazole-4-carbaldehyde - Visagaperumal, Dhanapal; Chandy, Vineeth (Anti-Infective Agents, 2020)
Background: In this study, synthesis of some novel 1-(3-(4-chlorophenylimino)-3,4- dihydroquinoxalin-2-yl)-3-substituted phenyl-1H-pyrazole-4-carbaldehyde were done by cyclization of dehydrated hemiketal using VilsmeierHaack reaction. The structures of synthesized compounds were in accordance of the basis of IR, 1HNMR, Mass spectral data and elemental analyses. The synthesized compounds had given good yields and high purity. Methods: The antimicrobial activity of the synthesized compounds was preliminarily screened by paper disc diffusion technique. The determination of minimum inhibitory concentrations (MIC) of the synthesized compounds were done by using tube dilution method. Results and Conclusion: All the screened compounds showed antibacterial and antifungal activity against selected strains of Gram positive and Gram negative bacteria and two strains of fungus, respectively but exhibited considerably less activity when compared to the reference drug ciprofloxacin and Fluconazole for antibacterial and antifungal activity, respectively. Among the synthesized compounds VV5 exhibited significant activity.
Keywords: 1HNMR